Laser Doppler Blood-Flow Signals from Human Teeth during an Alignment and Leveling Movement Using a Superelastic Archwire. (19th September 2013) - Salles, Alvaro Wagner Rodrigues; Salles, Adriana Mirian Cotrim; Nogueira, Gessé Eduardo Calvo
Abstract : Objective . The purpose of this study was to examine alterations in blood-flow signals (BFS) from human teeth during an alignment and leveling phase (superelastic wire 0.014′′) in a clinical orthodontic treatment using laser doppler flowmetry (LDF). Materials and Methods . Recordings were made in 12 maxillary left central incisors. The basal value of the BFS from each tooth (without orthodontic forces) was compared with the corresponding values of BFS during four periods of observation: 20 minutes, 48 hours, 72 hours, and one month after the activation of the orthodontic appliance. Results . Statistically significant decrease of BFS was observed at 20 minutes, 48 hours, and 72 hours ( P < 0.05 ) . No differences were found comparing BFS on day 30 and the corresponding basal values. Conclusion . Under real clinical conditions, a significant decrease in BFS was verified during the initial phase of the treatment, followed by a recovery on day 30.